Life history of Sacculina carcini Thompson, 1836 (Cirripedia: Rhizocephala: Sacculinidae) and the intermoult cycle of its host, the shore crab Carcinus maenas (Linnaeus, 1758) (Decapoda: Brachyura: Carcinidae). Issue 4 (12th July 2018) - Lützen, Jørgen; Jensen, Knut Helge; Glenner, Henrik
Abstract: The dominant colour through the intermoult cycle of Carcinus maenas (Linnaeus, 1758 ) changes from green to orange, then to red. The external developmental stages of the rhizocephalan parasite Sacculina carcini  Thompson, 1836 are correlated with this cycle such that the youngest stages predominantly occur when the crabs are green, the intermediate stages when they are orange, and the oldest when they are red. Fouling by the barnacle Balanus crenatus Bruguière, 1789 increases through this cycle as well, with both sacculinised and unparasitised crabs of orange or red colour being significantly more fouled than green crabs. Sacculinised green crabs with younger external parasite stages are generally least fouled, whereas orange and red crabs with late parasite stages are most fouled, but only female crabs show a statistically significant positive association between Sacculina infection and fouling. For both sexes, time since moulting, indicated by crab colour, is the most important predictor for fouling by B. crenatus .